If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6) * 2 = 169 Reorder the terms: (6 + x) * 2 = 169 Reorder the terms for easier multiplication: 2(6 + x) = 169 (6 * 2 + x * 2) = 169 (12 + 2x) = 169 Solving 12 + 2x = 169 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = 169 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 169 + -12 2x = 169 + -12 Combine like terms: 169 + -12 = 157 2x = 157 Divide each side by '2'. x = 78.5 Simplifying x = 78.5
| M-6m-7m-4= | | 4.9+z=-6 | | 12-x/8=20 | | 5y+10-7y= | | 1250/20 | | -2+y+0.6x=0.6x-0.5 | | 8*x-7=6*x+12 | | x+6+2x-5.5=(2x+.75)2 | | 4(x-5)=6(-x+2) | | 24n=30/100 | | 270=-9x | | x-6+2x-5.5=(2x+7.5)2 | | 10(s+3)=-37 | | -2.4n-4=-16 | | n10=40/25 | | 5x(8x-2)=130 | | 200-25+35x=h | | 0.09Xx=95.61 | | X^2+2x+50+5x+50=90 | | 8cos-5=0 | | 8-2(6n+1)= | | 11m^2-15m^2= | | X^2+2x+50+5x+50= | | 6(x-2)-4x+92=17 | | 20x^2y+4x^2+16x= | | 14x-13=9x | | 5=[30-(6-1)2] | | (-3)+(1)= | | 8/12=12n | | 2/5r- | | (1/3)/x=14/30 | | n2=50/20 |